MODEL EVALUASI LAHAN MENGGUNAKAN ENTROPY-MODIFIED ANALYTIC HIERARCHY PROCESS UNTUK OPTIMASI ALOKASI TANAMAN - , Tri Kuntoro Priyambodo, Drs.,M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The lack of the ability to decide the proper plant in the land-use planning makes Indonesia has no agriculture product priority to be exported. Another disadvantage in using manual land evaluation is the limitation of land area to be evaluated. It still left a problem to evaluate a wide area such as watershed. For that reasons, it needs a framework of integrated land-evaluation, multi criteria decision analysis, and land-use planning optimization which is user-friendly and ease all the stake holders to make a decision anytime from anywhere. The proposed model is based on thermodynamics theory especially entropy equilibrium in order to modify AHP which used in Multi-Criteria Decision Analysis. This dissertation proposed a model of land use optimization model in order to facilitates farmer, land-owner, government, planner, or other stake holders to make the best decision. The model is implemented as a web-based loosely coupled MCDA-GIS called Jala Peta Maya. Testing of the model has been conducted in Bogowonto watershed. It is obtained that the implemen tation of the model works well within the framework of thought. The result proves that the entropy-modified model gives a better crops allocation map.